MODEL LOYALITAS PELANGGAN BERBASIS CUSTOMER RELATIONSHIP MANAGEMENT (Studi Kasus pada Usaha Distro Districtsides dan Smith Semarang) - Agustina Maulidatur Rika (Jurnal Ekonomi dan Bisnis, 2017)
This study aimed to describe and analyze the effect of customer relationship managementon customer loyalty to the brand trust and customer satisfaction as an intervening variable.The population used is that consumers who buy at Distro Districtsides and Smith Semarang.By using purposive sampling technique, which specializes in consumer buying in distributionsDistrictsides and Smith Semarang minimum age of 20 years and above, then obtaineda sample size of 100 respondents. A tool of analysis is path analysis with SPSS, wherepreviously tested the validity and reliability and classic assumption test. The test results indicateCustomer Relationship Management positive and significant impact on brand trust. CustomerRelationship Management has a positive and significant impact on customer satisfaction. Thetrust has a positive and significant impact on customer satisfaction. Customer RelationshipManagement, brand trust and gratification of customers also have a positive and significantimpact on customer loyalty. The test results Sobel test shows that brand trust is able to becomean intervening variable between Customer Relationship Management to customer satisfaction.Customer satisfaction is able to become an intervening variable between brand trust andloyalty of customers. Brand trust is able to become an intervening variable between CustomerRelationship Management on customer loyalty. Customer satisfaction is able to be variableintervening between Customer Relationship Management on customer loyalty.Keywords: Customer Relationship Management, brand trust, customer satisfaction andcustomer loyalty